Production of Biodiesel From Palm Olein With The Aid Of Methanol And Potassium Hydroxide Catalyst - Felix Ishola, Angela Mamudu, Damola Adelekan, Francis Elehinafe, Felix Iyala, Salawu Enesi (International Journal of Advanced Science and Technology, 2020)
The rapid growth of industrialisation has resulted in an ever-increasing demand for energy, with fossil fuels being an essential source of fuel for vehicles in the transport sector of countries. The world fossil fuel reserve is fast depleting, and also, it dissipates unhealthy emissions, this, has led to researches to seek sustainable alternatives in biofuels production. The authors experimented with the production of biodiesel from refined, bleached and deodorized palm olein (RBD) extracted from unrefined palm oil (UPO). Despite being considered as a feasible biodiesel feedstock, scanty reports had been found on the processing of biodiesel from palm olein compared to other oils from the palm tree. The transesterification of RBD palm olein with methanol and potassium hydroxide (KOH) as catalyst yielded biodiesel with an average yield greater than 50% in this experimental work. The derived biodiesel has a density of 0.884 g/ml and a flashpoint of 208°C, which is equivalent to ASTM D975 for biodiesel fuels. This result has proven this technique viable and will serve as a reference for continuous research on the biofuel production process.